Aggressive forward infinite dimensional entangled state pair with reputation based weighted hub selection to packet loss avoidance. (19th November 2021) - Regin, R.; Murali, J.; Kumar, S. Pradeep; Karthik, C.; Kasilingam, C.
Mobile ad hoc network (MANET) is indeed a series of nodes that have been put with others to collaborate without infrastructure. In this paper first proposes an aggressive forward infinite-dimensional entangled pair state (AFIDEPS) that initiates pair state by allocating the key to the server and routing the key to that node afterward. When mapping keys into the hubs, area administration, and traditional name provides a direct mapping of values from keys. The proposed algorithm is a thin membrane designed to connect the lines, unless the Euclidean measure is indeed the metric demarcated on the axis. Next the reputation-based weighted hub selection (RWHS) route selection seems to be the process of choosing the best route in a network, from source to destination once the accumulation of resources increases each node network lifetime. The simulation process is implemented in NS2 with the percentage of reduction in packet loss of 96.5%.